Antropología, comunicación e imágenes: alternativas para pensar la publicidad y el consumo en la contemporaneidad - Trindade, Eneus; Ribeiro, José Da Silva (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2010)
We identify in this text, others procedures to study advertising and consumption images, in the perspective interdisciplinary of anthropology and communication. We observe that part of consumption process is made by incorporation and production of images, so this article shows, in its conclusion the necessity of methodological formulations for the works with visual anthropology of advertising and with the observation and registration photoetnografics of consumption situations to verify their productions of sense in cultural life.
Keywords: Advertising; Consumption; Anthropology; Images; Communication